Le Carnet d'expériences et d'observations au cycle 2 : un outil d'apprentissage scientifique pour l'élève ? - Catherine Boyer; Cora Cohen-Azria; Abdelkarim Zaïd (Nantes Université, 2016)
Since the 2000s, the pupils from kindergarten to secondary school have to use a new tool: the notebook of experiences and observations (CEO) which should develop learning, simultaneously improving the command over the language, group life, and the acquisition of scientific skills. The meaning of this learning constructed by the pupils, and of which the CEO keeps track, will be analysed with the help of the notion of subject consciousness developed by Yves Reuter (2003, 2007). It is defined as the manner in which the academic actors (re)construct academic disciplines and permits a closer look at the difficulties that pupils experience. This article therefore, presents some results of a study aimed at analysing how the consciousness of scientific disciplines is constructed by the pupils of kindergarten and grade 2 with the help of the CEO. What the CEO looks like? What are the actual activities carried out by the students? What do pupils retain of the use of the CEO? We will analyse the productions of the pupils whose entry into writing is difficult or easier, and will then cross-reference them with both interviews conducted at the end of their work and class observations.